The PC user's guide. - Anis, Nick; Menefee, Craig (Berkeley, USA : McGraw-Hill, Inc., 1991)
"The PC Users Guide is your one-step resource offering all the information you need to get up and running with your IBM® PC or compatible. Clearly written and easy to understand, The PC User's Guide is the only documentation you'll really want to have. PC experts Nick Anis and Craig Menefee provide you with comprehensive instructions for every IBM PC and compatible computer, including laptop and desktop models, and 386™ and 486™ microprocessor-based machines. The PC User's Guide begins by acquainting you with personal computer hardware components and how to set them up. After you have your system working, you'll learn about the • Operating system • Applications software • Disk drives and hard disks. You'll also find out about servicing your computer system, optimizing its performance, and upgrading or adding to it. From unpacking the box to tweaking the system, from BASIC to BIOS, The PC Users Guide is the book to reach for whenever you need help with your PC." (Copied from the paste).
Foreword. Acknowledgments. Introduction. One. Personal computers a basic guide. Two. Systems overview choosing a computer. Three. Unpacking and setting up. Four. Setting it up and turning it on. Five. Operating fundamentals. Six. Operating Systems and environments. Seven. Applications programs: getting your work done. Eight. Utilities-computer housekeepers. Nine. Working with DOS-the Basics. Ten. DOS and the hard disk. Eleven. Advanced DOS techniques and batch files. Twelve. DOS command reference. Thirteen. Introduction to Basic. Fourteen. Basic reference. Fifteen. Inside your computer. Sixteen. Understanding your hard disk. Seventeen. Getting the most from your system. Eighteen Troubleshooting, service, and repair. Appendix A. Glossary. Appendix B. Using the keyboard. Appendix C. Hard drives: geometries for cmos settings. Appendix D. DOS error messages. Appendix E. ASCII codes. Appendix F. How and where to buy a computer. Index.
Keywords: MICROCOMPUTERS -- TEACHING; COMPUTERS; OPERATIONAL SYSTEMS -- COMPUTERS; ELECTRONIC DATA PROCESSING; COMPUTER PROGRAMS; PROGRAMMING; DIGITAL ELECTRONIC COMPUTERS